Mesoptychia heterocolpos var. harpanthoides L. Soderstr. et Vana, Phytotaxa - Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Zenodo, 2014)
Mesoptychia heterocolpos var. harpanthoides (Bryhn et Kaal.) L.Söderstr. et Váňa, Phytotaxa 65: 53, 2012 (see Váňa et al. 2012e). BASIONYM: Lophozia harpanthoides Bryhn et Kaal., Rep. Second Norweg. Arctic Exped. 11: 33, 1906 (see Bryhn 1906). Published as part of Söderström, Lars, Hagborg, Anders & Konrat, Matt Von, 2014, Early Land Plants Today: Index of Liverworts & Hornworts 2011 - 2012, pp. 61-85 in Phytotaxa 170 (2) on page 71, DOI:10.11646/phytotaxa.170.2.1, http://zenodo.org/record/4779611